Legal Study on Waste Management on the Coastal Dadap Indramayu Coast in Waste Reduction and Handling from the Perspective of Indramayu Regency Regional Regulation Number 12 of 2016 - Trisna Sagita, Anggi; Yusup Permana, Deni; Dikrurahman, Diky; Ibrahim, Satrio M (Jurnal Legisci, 2025)
The waste problem at Dadap Beach, Indramayu, is a critical issue impacting the environment, ecosystems, and the local economy. Plastic waste, as the dominant component, threatens coastal sustainability and reduces the attractiveness of the area as a tourist destination. This study aims to analyze the implementation of Regional Regulation of Indramayu Regency Number 12 of 2016 regarding waste reduction and management in this region. The research employs an empirical legal method with a qualitative approach, focusing on field data collection through interviews and observations. The findings indicate that waste reduction is carried out through community education and the provision of segregated trash bins, though these efforts are not optimal due to low public awareness and a lack of supporting facilities such as 3R TPS (Reduce, Reuse, Recycle facilities) and waste banks. Waste management involves collection by the village and transportation to final disposal sites (TPA) by the Environmental Agency (DLH) under a retribution scheme, which poses a significant challenge due to the village's limited budget. Furthermore, Dadap Village's geographical location as a downstream area exacerbates waste accumulation from upstream river flows. The study concludes that the implementation of the regulation has not been effective due to systemic barriers such as inadequate infrastructure, weak law enforcement, and insufficient cross-sector collaboration. Recommendations include enhancing public education, strengthening infrastructure, optimizing budgets, and developing local innovations for sustainable waste management. These measures are expected to restore Dadap Beach to a clean, healthy, and productive coastal environment.